2020
DOI: 10.1101/2020.09.21.305953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antioxidant enriched fraction fromPueraria tuberosaalleviates ovariectomized-induced osteoporosis in rats, and inhibits growth of breast and ovarian cancer cell linesin vitro

Abstract: Pueraria tuberosa (P. tuberosa), known as Indian Kudzu belongs to family Fabaceae and it is solicited as “Rasayana” drugs in Ayurveda. In the present study, we analyzed the efficacy an antioxidant enriched fraction (AEF) from the tuber extract of P. tuberosa against menopausal osteoporosis and breast and ovarian cancer cell lines. The AEF from P. tuberosa was identified by determining phenolic composition (total phenolic and flavonoid amount). Antioxidant property (in vitro assays) was also carried out followe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, the mechanism behind this activity needs exploration for therapeutic use ( Satpathy et al, 2018 ). Antioxidant-enriched fraction also exhibited in vitro cytotoxicity in the breast (MCF-7 and MDA-MB-231) and ovarian (SKOV-3) cancer cells ( Satpathy et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanism behind this activity needs exploration for therapeutic use ( Satpathy et al, 2018 ). Antioxidant-enriched fraction also exhibited in vitro cytotoxicity in the breast (MCF-7 and MDA-MB-231) and ovarian (SKOV-3) cancer cells ( Satpathy et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies also showed a considerable decrease in the quantity of mature Leydig cells, cauda epididymis, and sperm motility ( Gupta et al, 2005 ). The antioxidant-enriched fraction from the tuber extract of P. tuberosa against menopausal osteoporosis in ovariectomy-induced osteoporosis in rats was studied and found that it improved biochemical parameters, controlled the increased body weight, and decreased uterus weight following ovariectomy as well as restoration of typical bone structure and trabecular width of the femur ( Satpathy et al, 2020 ). Incision and excision wounds were treated with methanolic and ethyl acetate tuber extract of P. tuberosa .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro cytotoxicity and anticancer activities [28] Formononetin human osteosarcoma cell lines (U2OS)/0-80 µM…”
Section: Assessment Of Cytotoxic Activitiesmentioning
confidence: 99%
“…Recently, various studies have been conducted to survey the cytotoxic activity of plant-derived compounds, such as isoflavones, against human cancer cells [ 28 , 29 ]. Despite the extensive investigation of their promising biological potentials, the study of possible cytotoxic potency of isoflavones remains important.…”
Section: Introductionmentioning
confidence: 99%